A Case of Metastasis to the Caude Equina from Lung Carcinoma - Takara, Hiroaki; Nisihira, Takeshi; Kuniyoshi, Shinya; Kinjyou, Yukio; Ibaraki, Kunio (Orthopedics & Traumatology, 1992)
Spinal intradural metastasis originating from outside the neural axis is extremely rare. We therefore will report a case of metastasis to the cauda equina from lung carcinoma. The clinical course may be so rapid and poor that operative treatment should be considered after careful clinical evaluations.